Dynamics and financing of the strategic investments - Bukvič, Vladimir (Advances in business related scientific research journal, 2024)
The author shows how companies in the real sector of the economy carry out their investment activities, especially how they invest in long-term assets, in terms of both investment dynamics and investment financing, with an emphasis on strategic investments. In the theoretical part of the paper, the author presents certain laws that apply in the field of investment activity, addressing the issue of the intensity of the investment activity of companies over time and the issue of providing the necessary financial resources for the implementation of strategic investments. In the empirical part of the paper, on a sample of Slovenian large and medium-sized companies from the real sector of the economy, the investment activity of companies in the period 2010–2017, i.e. after the great financial crisis and economic recession, is shown. This is done through the prism of various factors and their effects on investment ability. The author puts forward several research hypotheses (7), which he fully confirms
Keywords: investment ability; investment dynamics; investment financing; investment opportunities; strategic investments